The Genealogy of Hadith Criticism Methods in Western Scholarship - Imam Sahal Ramdhani; Al Makin; Ja'far Assagaf (ESENSIA: Jurnal Ilmu-Ilmu Ushuluddin, 2025)
The historicity of hadith is a prominent topic in debates concerning hadith criticism methods within Western hadith scholarship. The issue lies in the fact that the methods developed by Western revisionist hadith scholars, primarily based on the written tradition, tend to marginalize sources of hadith historicity grounded in the oral tradition. Consequently, Western revisionist hadith scholarship often provides an unbalanced justification and generalization of hadith historiography. Addressing this concern, this article employs a genealogical approach alongside Michel Foucault’s theory of power relations in knowledge to trace, examine, and evaluate the methods of hadith criticism that have emerged within Western scholarship. The findings of this research are as follows: first, the methods of hadith criticism developed by Western revisionist scholars are founded upon a Eurocentric paradigm that dominates and exerts hegemony over the history of hadith. This paradigm centers on the primacy of the written tradition’s validity. Second, the methods developed by the revisionist group are ultimately rooted in a network of knowledge-power, which is interconnected and exerts hegemonic control over the discourse